Chronological problems with sites of the Primorskaya culture on the north-eastern coast of the Vistula Lagoon - Zaltsman, Edwin (Instytut Archeolgoii i Etnologii Polskiej Akademii Nauk, 2016)
The paper focuses on the chronology of the eastern group of the Primorskaya culture, introducing a new series of radiocarbon dates. Materials obtained from features with their foundations sunk into the ground and from cultural layers of the settlements Pribrezhnoye and Ushakovo-3 are described in the context of C-14 datings. The original nature of CWC sites from the north-western coast of the Vistula Lagoon is shown on the basis of C-14 dating, specific traits of ceramic assemblages and properties of the material culture
ill. ; 25 cm
Keywords: north-eastern coast of the Vistula Lagoon; Kaliningrad region (Russia); Primorskaya culture; Corded Ware culture; Globular Amphora culture; C-14 dating